KONSUMEN DALAM PERSAINGAN SEMPURNA: BAGAIMANA MENAKLUKKAN PASAR PERSAINGAN SEMPURNA DI PASAR TRADISIONAL? - Aditya Willy Ramadhan; Budi Setiawan; Edi Dwi Cahyono (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Perfect competition in the pasar gedhe results in product pricing that cannot be determined unilaterally by producers. As a result, product prices do not serve as the sole reference that attracts consumers to purchase from Restu Buah over similar products from competitors in the pasar gedhe. Ideally, this situation should allow consumers to freely switch producers to meet their product needs. However, in reality, consumers exhibit loyalty to Restu Buah, even when its prices are comparable to those of competitors in the pasar gedhe. The aim of this study is to analyze the influence of service quality, product quality, and price perception on customer satisfaction at Restu Buah in the pasar gedhe, Solo. The target respondents for this study are customers of Restu Buah. Respondents are selected based on several criteria that must be met. A total of 130 respondents will be involved in this research. They will be given a questionnaire containing questions rated on a scale of 1-4 related to the study. This research will use two types of data collection: primary data and secondary data. The collected data will be analyzed using the SEM-PLS analysis method with Warp-PLS 8.0 software. The research results indicate that service quality, product quality, and price perception have a positive and significant effect on customer satisfaction, with an R-squared value of 0.71. This value indicates that service quality, product quality, and price perception can explain 71% of customer satisfaction, while the remaining 29% is attributed to other variables not tested in this study. Service quality, product quality, and price perception have a positive and significant impact on customer satisfaction at Restu Buah.